Influence of Intraseasonal Variability on the Development of Monsoon Depressions - Nirupam Karmakar; William R. Boos; Vasubandhu Misra (Geophysical Research Letters)
Abstract Previous studies showed that the activity of monsoon low‐pressure systems (LPS), which produce a large fraction of the South Asian monsoon's total rainfall, is modulated by intraseasonal variability. Using satellite‐derived products and atmospheric reanalyzes, this study examines how the boreal summer intraseasonal oscillation (ISO) separately modulates the occurrence of weaker LPS (lows) and stronger LPS (depressions). It is found that the genesis of lows is insensitive to ISO phase, while depressions exhibit a strong preference for genesis during the phase that is convectively active over the northern Indian Ocean. Essentially, development of LPS into depressions depends upon the timing of genesis of the initial disturbance. Evidence is presented supporting the hypothesis that the development of lows into depressions is fostered by large‐scale atmospheric conditions governed by the ISO. Results also suggest that while lows have no preference for forming over ocean compared to land, depressions mostly form over ocean.